Stock-Bond Nexus: The Case of Malaysia - Pargan, Nuraznezan; Mustafa, Siti Aisyah (Research in Management of Technology and Business, 2020)
The dynamic behavior of stock and bond market movements over time has called for an appraisal of knowing their nexus. The increasing role of these two market segments in the Malaysian economy amplifies the need for such information. Hence, in this study, we examine the causality linkage between in daily observations of stock index and bond yield movements in the Malaysian market. A cointegration method, namely autoregressive distributed lag (ARDL) model is employed to investigate both the short-run and long-run causality on a set of daily stock price index and 10-year government bond yield from the period spanning 2008 to 2018. The findings of the study indicated that the model variables have no long-run and short-run interactions, but the causality test result suggests that FBMKLCI causes MGS 10-year yield in this study which is uni-directional.